Diversification of Prochilodus in the eastern Brazilian Shield: Evidence from complete mitochondrial genomes (Teleostei, Prochilodontidae) - Santos, Rosiane P.; Melo, Bruno F. [UNESP]; Yazbeck, Gabriel M.; Oliveira, Rafael S.; Hilario, Heron O.; Prosdocimi, Francisco; Carvalho, Daniel C. (Wiley-Blackwell, 2021)
The Neotropical fish genus Prochilodus includes five species occurring in the main drainages of the eastern Brazilian Shield: P. argenteus, P. costatus, P. lineatus, P. harttii, and P. vimboides. Multi and single locus phylogenies have questioned the monophyly of P. costatus and P. lineatus, and the biogeographic history of these species in the Brazilian Shield has never been explored. We characterized new mitogenomes for these species to reconstruct their evolutionary history, estimated the timing of Prochilodus cladogenesis, and discussed the implications of past geologic events on species diversification. The phylogeny supports the monophyly of both P. costatus and P. lineatus, and indicates a Miocene divergence of P. vimboides, much earlier than subsequent species diversification. The Early Pleistocene split of P. argenteus and P. harttii (similar to 2.1 million years ago-MYA) is hypothesized to be related to recent Quaternary reactivations of the Rio Aracuai Fault that promoted river captures between the eastern tributaries of the Sao Francisco basin and the upper Rio Jequitinhonha in the Serra do Espinhaco mountain range. The time-calibrated phylogeny also indicated a subsequent split of P. costatus and P. lineatus (similar to 1.1 MYA) likely due to Quaternary activities of the Upper Rio Sao Francisco crustal discontinuity and Estrela Fault that catalyzed river captures between the upper Rio Sao Francisco and the Rio Grande of the Parana basin in the Serra da Canastra mountain range. These results provide a temporal context for the diversification of Prochilodus and bring new insights to further study the historical biogeography of other riverine fish groups along the upland basins of the eastern Brazilian Shield.
Keywords: biogeography; freshwater fishes; mitogenomics; neotropics; paleogeography